Overweight in adolescents: moderating role of gender and mother’s education level - Bacil, Eliane Denise Araújo (2016)
Objective: To investigate the moderating effect of gender and mother’s education level on the relation between overweight and associated factors in adolescents. Methods: This is a descriptive cross-sectional study, performed with 945 students, of both sexes, aged between 14 and 18 years, of Ponta Grossa, Paraná. Weight and height measurements were collected. The adolescents filled out a questionnaire addressing sociodemographic information (gender, age, occupation/work, adolescent’s address and parents’ level of education), sedentary behavior (time watching TV/at the computer), participation in Physical Education classes and practice of physical activities. For data analysis, Poisson regression was used in STATA 9.2 software, adopting a significance level of p